The Probiotic Bacillus subtilis MB40 Improves Immunity in a Porcine Model of Listeriosis - Sean M. Garvey; Nima K. Emami; Justin L. Guice; Nammalwar Sriranganathan; Christopher Penet; Robert P. Rhoads; Jessica L. Spears; Rami A. Dalloul; Samer W. El-Kadi (Microorganisms, 2023)
Probiotics for humans and direct-fed microbials for livestock are increasingly popular dietary ingredients for supporting immunity. The aim of this study was to determine the effects of dietary supplementation of Bacillus subtilis MB40 (MB40) on immunity in piglets challenged with the foodborne pathogen Listeria monocytogenes (LM). Three-week-old piglets (n = 32) were randomly assigned to four groups: (1) basal diet, (2) basal diet with LM challenge, (3) MB40-supplemented diet, and (4) MB40-supplemented diet with LM challenge. Experimental diets were provided throughout a 14-day (d) period. On d8, piglets in groups 2 and 4 were intraperitoneally inoculated with LM at 108 CFU/mL per piglet. Blood samples were collected at d1, d8, and d15 for biochemical and immune response profiling. Animals were euthanized and necropsied at d15 for liver and spleen bacterial counts and intestinal morphological analysis. At d15, LM challenge was associated with increased spleen weight (p = 0.017), greater circulating populations of neutrophils (p = 0.001) and monocytes (p = 0.008), and reduced ileal villus height to crypt depth ratio (p = 0.009), compared to non-challenged controls. MB40 supplementation reduced LM bacterial counts in the liver and spleen by 67% (p < 0.001) and 49% (p < 0.001), respectively, following the LM challenge, compared to the basal diet. MB40 supplementation was also associated with decreased circulating concentrations of monocytes (p = 0.007). Altogether, these data suggest that MB40 supplementation is a safe and well-tolerated approach to enhance immunity during systemic Listeria infection.